Beyond Technicalities: Spiritual Motivation as a Mediator Between Academic Supervision and Teacher Performance - Musyaffa Rafiqie; Nik Haryanti; Muhammad Ihwan; Irfan Habibi; Sutarum Sutarum (JURNAL AL-TANZIM, 2026)
This study aims to analyse the effect of academic supervision on teacher performance with spiritual work motivation as a mediating variable in Islamic schools. This study used a quantitative, survey-based approach. The study population included all teachers in Islamic schools, and the sampling technique was total sampling. The research instrument was a questionnaire that had been tested for validity and reliability. Data analysis was conducted using path analysis to examine the direct and indirect effects between variables. The results showed that academic supervision had a positive and significant effect on teacher performance. Academic supervision also had a positive and significant effect on spiritual work motivation, which, in turn, positively and significantly influenced teacher performance. Important findings indicate that spiritual work motivation acts as a mediating variable, strengthening the influence of academic supervision on teacher performance. Academic supervision that is systematically implemented, humanistically oriented, and grounded in Islamic spiritual values can increase teachers' spiritual motivation, ultimately impacting teacher performance. This study provides theoretical and practical implications for Islamic school administrators in designing an academic supervision model that is not only oriented toward the technical aspects of learning but also emphasises strengthening spiritual motivation for teaching as an integral part of teacher professional development.